Large contribution of soil N2O emission to the global warming potential of a large-scale oil palm plantation despite changing from conventional to reduced management practices - G. Chen; G. Chen; E. Veldkamp; M. Damris; B. Irawan; A. Tjoa; M. D. Corre (Biogeosciences, 2024)
Conventional management of oil palm plantations, involving high fertilization rate and herbicide application, results in high yield but with large soil greenhouse gas (GHG) emissions. This study aimed to assess a practical alternative to conventional management, namely reduced fertilization with mechanical weeding, to decrease soil GHG emissions without sacrificing production. We established a full factorial experiment with two fertilization rates (conventional and reduced fertilization, equal to nutrients exported via fruit harvest) and two weeding methods (herbicide and mechanical), each with four replicate plots, since 2016 in a ≥ 15-year-old, large-scale oil palm plantation in Indonesia. Soil CO2, N2O, and CH4 fluxes were measured during 2019–2020, and yield was measured during 2017–2020. Fresh fruit yield (30 ± 1 Mg<mspace width="0.125em" linebreak="nobreak"/>ha-1<mspace linebreak="nobreak" width="0.125em"/>yr-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="62pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="57f846380ea793de7b2a1f91bd3c529e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-21-513-2024-ie00001.svg" width="62pt" height="15pt" src="bg-21-513-2024-ie00001.png"/></svg:svg>) and soil GHG fluxes did not differ among treatments (P≥ 0.11), implying legacy effects of over a decade of conventional management prior to the start of the experiment. Annual soil GHG fluxes were 5.5 ± 0.2 Mg CO2-C ha−1 yr−1, 3.6 ± 0.7 kg N2O-N ha−1 yr−1, and −1.5 ± 0.1 kg CH4-C ha−1 yr−1 across treatments. The palm circle, where fertilizers are commonly applied, covered 18 % of the plantation area but accounted for 79 % of soil N2O emission. The net primary production of this oil palm plantation was 17 150 ± 260 kg<mspace linebreak="nobreak" width="0.125em"/>C<mspace linebreak="nobreak" width="0.125em"/>ha-1<mspace width="0.125em" linebreak="nobreak"/>yr-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="68pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="62f4bff4307f60295cbef239a7f84956"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-21-513-2024-ie00002.svg" width="68pt" height="15pt" src="bg-21-513-2024-ie00002.png"/></svg:svg>, but 62 % of this was removed by fruit harvest. The global warming potential of this planation was 3010 ± 750 kg<mspace width="0.125em" linebreak="nobreak"/>CO2<mspace linebreak="nobreak" width="0.125em"/>eq<mspace linebreak="nobreak" width="0.125em"/>ha-1<mspace width="0.125em" linebreak="nobreak"/>yr-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="94pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="4069fc3755283d1dd599f670665b4d2e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-21-513-2024-ie00003.svg" width="94pt" height="16pt" src="bg-21-513-2024-ie00003.png"/></svg:svg>, of which 55 % was contributed by soil N2O emission and only < 2 % offset by the soil CH4 sink.